Inflation and counter-inflationary policy measures: The case of Greece - Chrestos *ca. 20./21. Jh.* Pierros; Sotiria *ca. 20./21. Jh.* Theodoropoulou (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
This chapter examines the recent evolution of inflation and its drivers in Greece, as well as the policies undertaken to limit its increase and mitigate its impact on households and firms. Greece is an interesting case as the current inflationary episode and the challenges it creates for real incomes is the third major economic shock that the country and its population have undergone since 2010, following the public debt crisis and the Covid-19 pandemic, from which the economy had just recovered. As elsewhere in the Euro Area, energy inflation has been the main driver of the Greek headline inflation and we illustrate the various reasons why this has been so, most notably the high natural gas distribution costs (a consequence of high market concentration) with its impact on electricity costs, and the elevated indirect taxes on energy. Inflation has had a detrimental effect on wage earners in Greece with real wages falling, while the wage share has also been in steady decline. Profit shares have been holding up or even increasing, suggesting a regressive effect from inflation. The Greek government has been going to great lengths to mitigate the impact of energy inflation on households and companies and to limit its rise, spending €9.8bn or 5.4% of GDP between September 2021 and October 2022, the fourth highest percentage of GDP in the EU, mostly on horizontal subsidies, without income criteria, or, until October 2022, even any incentives to reduce energy demand. A preliminary assessment of these measures suggests that inadequate targeting of vulnerable households means that, despite the high levels of expenditure, policy has not substantially alleviated the regressive impact of inflation, especially on households with lingering financial fragility from the previous two economic shocks experienced since 2010.
urn:nbn:de:101:1-2023011910362914486199
Keywords: 330; Inflation; Greece; gas; electricity; price cap; HICP; energy; distribution; social pact; real wages